Operational C-Band Dual-Polarization Radar QPE for the Subtropical Complex Terrain of Taiwan - Yadong Wang; Jian Zhang; Pao-Liang Chang; Carrie Langston; Brian Kaney; Lin Tang (Advances in Meteorology)
Complex terrain poses significant challenges to the radar based quantitative precipitation estimation (QPE) because of blockages to the lower tilts of radar observations. The blockages often force the use of higher tilts data to estimate precipitation at the ground and result in errors due to vertical variations of the radar variables. To obtain accurate radar QPEs in the subtropical complex terrain of Taiwan, a vertically corrected composite algorithm (VCCA) was developed for two C-band polarimetric radars. The new algorithm corrects higher tilt radar variables with the vertical profile of reflectivity (VPR) or vertical profile of specific differential phase (VPSDP) and estimates rainfall rate at the ground through an automated combination of R-Z and R-KDP relations. The VCCA was assessed with three precipitation cases of different regimes including typhoon, mei-yu, and summer stratiform precipitation events. The results showed that a combination of R-Z and R-KDP relations provided more accurate QPEs than each alone because R-Z provides better rainfall estimates for light rains and R-KDP relation is more suitable for heavy rains. The vertical profile corrections for reflectivity and specific differential phase significantly reduced radar QPE errors caused by inadequate sampling of the orographic enhancement of precipitation near the ground.